Keberlangsungan Menetap Penduduk Asli Pada Kawasan di Sekitar Kampus UNDIP Tembalang Sebagai Permukiman Kota Semarang yang Tergentrifikasi - Prayoga, I Nyoman Tri (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Tembalang area, Semarang, has been identified to experience gentrification (Prayoga, 2011). Gentrification is understood as the changing of social-economic status of an area which has formerly been inhabited by lower income natives, and then substituted by new settlers with higher income, along with increasing activity and investment in the area (Glass, 1963 in Gur, 2009). This study applies case study qualitative approach in examining the vulnerability of natives leaving the area, and their survival pattern to maintain their residence in the midst of the gentrification and rapid flow of new, higher income setters. The study also examines the perception of the natives towards the new settlers and the on going changes. Explanatory analysis indicated that the natives realize that their residence possess strategic advantage in terms of living and economic. They adapt by capturing business opportunities to improve their welfare and standards of living. In general the natives realizes the impacts, whether positive or negative, of the changes going on around them along with the arrival of new settlers, departure of fellow natives, and physical transformation towards an urban environment. The study has indicated that the natives have also tries to acknowledge the changes wisely.